Positive electrode active material for lithium-ion secondary batteries and method for manufacturing the same
Patent Information
- Application Number
- JP2025059558
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166558000001 
Figure 2026166558000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to a positive electrode active material for lithium-ion secondary batteries and a method for producing the same. [Background technology]
[0002] In recent years, research and development has been conducted on secondary batteries that contribute to energy efficiency in order to ensure that more people have access to affordable, reliable, sustainable, and advanced energy. Lithium transition metal oxides, mainly composed of transition metals such as nickel, cobalt, and manganese, are commonly used as positive electrode active materials for lithium-ion secondary batteries. The application of a coating layer to the surface of lithium transition metal oxides is being considered (Patent Documents 1 and 2). [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Special Publication No. 2023-513558 [Patent Document 2] Japanese Patent Publication No. 2021-64598 [Overview of the project] [Problems that the invention aims to solve]
[0004] Incidentally, resource sustainability is one of the challenges in secondary battery technology. In lithium transition metal oxides, the sustainability of cobalt is considered important. For this reason, the use of lithium-nickel-manganese composite oxide, which contains lithium, nickel, and manganese but does not contain cobalt, is being considered as a positive electrode active material. However, lithium-nickel-manganese composite oxide has a lower discharge capacity compared to lithium transition metal oxides that contain cobalt.
[0005] This invention has been made in view of the above-mentioned problems, and aims to provide a lithium-nickel-manganese composite oxide with improved discharge capacity and a method for producing the same. Ultimately, this contributes to energy efficiency. [Means for solving the problem]
[0006] The inventors of the present invention have discovered that the discharge capacity can be improved by coating a portion of the surface of a lithium-nickel-manganese composite oxide with a coating layer containing boron, and have completed the present invention. Accordingly, the present invention provides the following:
[0007] (1) A positive electrode active material for a lithium-ion secondary battery, comprising a lithium-nickel-manganese composite oxide containing lithium, nickel, and manganese but not cobalt, and a coating layer covering a portion of the surface of the lithium-nickel-manganese composite oxide, wherein the coating layer contains boron and the coverage rate of the coating layer is 40% or more and 90% or less.
[0008] According to the positive electrode active material for lithium-ion secondary batteries in (1), the lithium-nickel-manganese composite oxide does not contain cobalt, thus making it highly sustainable in terms of resources. Furthermore, since the surface of the lithium-nickel-manganese composite oxide is covered with a boron-containing coating layer at the above coverage rate, the discharge capacity is improved.
[0009] (2) A positive electrode active material for lithium-ion secondary batteries as described in (1), wherein the boron content is 0.25% by mass or more and less than 0.75% by mass in terms of boric acid.
[0010] (2) According to the positive electrode active material for lithium-ion secondary batteries, the boron content forming the coating layer is within the above range, so the discharge capacity is reliably improved.
[0011] (3) The positive electrode active material for lithium-ion secondary batteries according to (1) or (2), wherein the coating layer contains boric acid.
[0012] According to the positive electrode active material for lithium ion secondary batteries of (3), the boric acid contained in the coating layer has low reactivity and is chemically stable, so the discharge capacity is improved over a long period of time.
[0013] (4) The positive electrode active material for lithium ion secondary batteries according to any one of (1) to (3), wherein the thickness of the coating layer is 5.0 nm or more and 20.0 mm or less.
[0014] According to the positive electrode active material for lithium ion secondary batteries of (4), the thickness of the coating layer is within the above range and is large, so the discharge capacity is more reliably improved.
[0015] (5) The positive electrode active material for lithium ion secondary batteries according to any one of (1) to (4), wherein the average primary particle diameter of the lithium-nickel-manganese composite oxide is 3 μm or more and 5 μm or less.
[0016] According to the positive electrode active material for lithium ion secondary batteries of (5), the average primary particle diameter is within the above range and is fine, so the discharge capacity increases.
[0017] (6) The positive electrode active material for lithium ion secondary batteries according to any one of (1) to (5), wherein the ratio of the thickness of the coating layer to the average particle diameter of the lithium-nickel-manganese composite oxide is 0.001 or more and 0.014 or less.
[0018] When the ratio of the thickness of the coating layer to the average particle diameter of the lithium-nickel-manganese composite oxide in (6) is within the above range, the balance between the electric capacity per particle of the lithium-nickel-manganese composite oxide and the thickness of the coating layer is good, and the discharge capacity is further improved.
[0019] (7) The positive electrode active material for lithium ion secondary batteries according to any one of (1) to (6), wherein the amount of hydrochloric acid required to neutralize a mixed liquid obtained by putting 1 g of the positive electrode active material for lithium ion secondary batteries into 50 mL of water with 0.05 mol / L hydrochloric acid is 1.8 mL or more and 2.9 mL or less.
[0020] (8) A method for producing a positive electrode active material for a lithium-ion secondary battery, comprising calcining a mixture containing lithium, nickel, and manganese, but without cobalt, and boric acid, in a ratio such that the boric acid content is 0.25% by mass or more and less than 0.75% by mass.
[0021] According to the method for producing a positive electrode active material for lithium-ion secondary batteries of (8), since a mixture containing boric acid within the above range is calcined, a positive electrode active material for lithium-ion secondary batteries in which the surface of the lithium-nickel-manganese composite oxide is partially covered with a coating layer containing boron can be produced industrially advantageously. The resulting positive electrode active material for lithium-ion secondary batteries has improved discharge capacity because the surface of the lithium-nickel-manganese composite oxide is covered with a coating layer containing boron at the above coverage rate.
[0022] (9) The method for producing a positive electrode active material for a lithium-ion secondary battery according to (8), wherein the calcination temperature of the mixture is 200°C or more and 500°C or less.
[0023] According to the method for producing a positive electrode active material for lithium-ion secondary batteries in (9), since the firing temperature of the mixture is within the above range, the discharge capacity of the resulting positive electrode active material for lithium-ion secondary batteries is reliably improved.
[0024] (10) A method for producing a positive electrode active material for a lithium-ion secondary battery according to (9), wherein the material is heated to the firing temperature at a heating rate of 5°C / min or more and 20°C / min or less.
[0025] According to the method for producing a positive electrode active material for lithium-ion secondary batteries of (10), since the rate of heating up to the firing temperature is within the above range, the discharge capacity of the resulting positive electrode active material for lithium-ion secondary batteries is more reliably improved.
[0026] (11) A method for producing a positive electrode active material for a lithium-ion secondary battery according to any one of (8) to (10), wherein the calcination time of the mixture is 0.5 hours or more and 5.0 hours or less.
[0027] According to the method for producing a positive electrode active material for lithium-ion secondary batteries of (11), since the calcination time of the mixture is within the above range, the discharge capacity of the resulting positive electrode active material for lithium-ion secondary batteries is further reliably improved. [Effects of the Invention]
[0028] According to the present invention, it is possible to provide a lithium-nickel-manganese composite oxide with improved discharge capacity and a method for producing the same. [Modes for carrying out the invention]
[0029] The following describes embodiments of the present invention. However, the embodiments described below are illustrative and not limited to the present invention.
[0030] The positive electrode active material for the lithium-ion secondary battery of this embodiment comprises a lithium-nickel-manganese composite oxide and a coating layer that covers a portion of the surface of the lithium-nickel-manganese composite oxide.
[0031] The lithium-nickel-manganese composite oxide used in this embodiment contains lithium, nickel, and manganese, but does not contain cobalt. The average primary particle diameter of the lithium-nickel-manganese composite oxide may be, for example, 3 μm or more and 5 μm or less. The average primary particle diameter is the average of the particle diameters of 100 primary particles measured using a scanning electron microscope (SEM).
[0032] The coating layer covering the lithium-nickel-manganese composite oxide contains boron. The coating layer may also be, for example, boric acid or a thermal decomposition product of boric acid. The coverage rate of the coating layer is set to 40% or more and 90% or less. The coverage rate was calculated using the following formula by measuring the amount of boron (at%), nickel (at%), and manganese (at%) on the surface of the positive electrode active material for lithium-ion secondary batteries using XPS (X-ray photoelectron spectroscopy). In this embodiment, the coverage rate is the average value of the coverage rates measured for 100 positive electrode active materials for lithium-ion secondary batteries.
[0033] Coverage (%) = Amount of boron / (Amount of boron + Amount of nickel + Amount of manganese) × 100
[0034] The thickness of the coating layer may be, for example, between 5.0 nm and 20.0 nm. The thickness of the coating layer was determined to be the depth at which the boron concentration in the depth profiling becomes half. That is, the thickness of the coating layer was measured as follows: The surface of the positive electrode active material for lithium-ion secondary batteries was scraped off in 10 nm increments by sputtering, and the boron concentration on the scraped surface of the positive electrode active material for lithium-ion secondary batteries was measured by XPS to obtain a depth profiling profile. From the obtained depth profiling profile, the depth at which the boron concentration becomes half of the surface concentration was determined as the thickness of the coating layer. Note that the thickness of the coating layer in this embodiment is the average value of the thickness of the coating layer measured for 100 positive electrode active materials for lithium-ion secondary batteries.
[0035] The thickness of the coating layer may be 0.001 or more and 0.014 or less, as a ratio to the average particle diameter of the lithium-nickel-manganese composite oxide (thickness of the coating layer / average particle diameter of the lithium-nickel-manganese composite oxide).
[0036] The positive electrode active material for lithium-ion secondary batteries may have a boron content of 0.25% by mass or more and less than 0.75% by mass in terms of boric acid equivalent. The boron content is obtained as follows: The positive electrode active material for lithium-ion secondary batteries is dissolved in acid, and the boron concentration in the resulting solution is measured. The obtained boron concentration is converted to a boric acid concentration, and the boric acid content of the positive electrode active material for lithium-ion secondary batteries is calculated.
[0037] For lithium-ion secondary batteries, the amount of hydrochloric acid required to neutralize a mixture obtained by adding 1 g of the positive electrode active material to 50 mL of water with 0.05 mol / L hydrochloric acid (to bring the pH of the mixture to 7) may be between 1.8 mL and 2.9 mL. This amount of hydrochloric acid corresponds to the amount of basic components (water-soluble lithium salts) remaining on the surface of the lithium-ion secondary battery positive electrode active material.
[0038] The positive electrode active material for lithium-ion secondary batteries of this embodiment can be produced, for example, by calcining a mixture containing a lithium-nickel-manganese composite oxide and boric acid in a ratio such that the boric acid content is 0.25% by mass or more and less than 0.75% by mass.
[0039] The mixing of lithium-nickel-manganese composite oxide and boric acid can be carried out by a dry method. Alternatively, a high-speed agitator can be used for mixing the lithium-nickel-manganese composite oxide and boric acid.
[0040] The atmosphere during firing of the mixture is not particularly limited and may be an air atmosphere. The firing temperature of the mixture may be, for example, 200°C to 500°C or 250°C to 450°C. The heating rate to the firing temperature may be, for example, 5°C / min to 20°C / min. The firing time may be 0.5 hours to 5 hours or 1.0 hour to 4.0 hours.
[0041] The positive electrode active material for lithium-ion secondary batteries of this embodiment can be used as the positive electrode active material for lithium-ion secondary batteries. A lithium-ion secondary battery has, for example, a positive electrode, a negative electrode, an electrolyte, a separator placed between the positive and negative electrodes, and an outer casing that houses these components. A solid electrolyte may be used instead of the electrolyte.
[0042] The positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the surface of the positive electrode current collector. The positive electrode active material layer includes the positive electrode active material for lithium-ion secondary batteries of this embodiment. The positive electrode active material layer may also include a conductive additive and a binder. The conductive additive and binder are not particularly limited, and known ones used in the positive electrode active material layer of lithium-ion secondary batteries can be used. The positive electrode current collector is also not particularly limited, and known ones used in the positive electrode current collector of lithium-ion secondary batteries, such as aluminum foil, can be used.
[0043] As the negative electrode, a laminate comprising a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector can be used. The negative electrode active material layer contains negative electrode active material. As the negative electrode active material, metallic lithium, a substance capable of intercalating and releasing lithium, and a metal or metalloid that forms an alloy with lithium can be used. Examples of substances capable of intercalating and releasing lithium include lithium transition metal oxides such as lithium titanate, transition metal oxides such as TiO2, Nb2O3, and WO3, SiO, metal sulfides, metal nitrides, and carbon materials such as artificial graphite, natural graphite, graphite, soft carbon, and hard carbon. Examples of metals or metalloids that form an alloy with lithium include Mg, Si, Au, Ag, In, Ge, Sn, Pb, Al, and Zn. If the negative electrode active material is in powder form, the negative electrode active material layer may contain a conductive additive and a binder. There are no particular restrictions on the conductive additive and binder, and known ones used in the negative electrode active material layer of lithium-ion secondary batteries can be used. Furthermore, there are no particular restrictions on the negative electrode current collector; known materials used in the negative electrode current collectors of lithium-ion secondary batteries, such as copper foil, can be used.
[0044] The electrolyte contains an organic solvent and an electrolyte. Examples of organic solvents include cyclic carbonates, linear carbonates, cyclic ethers, linear ethers, hydrofluoroethers, aromatic ethers, sulfones, cyclic esters, linear carboxylic acid esters, and nitriles. Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate. Examples of linear carbonates include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Examples of cyclic ethers include tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,3-dioxolane, and 4-methyl-1,3-dioxolane. Examples of linear ethers include 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, and diethyl ether. Examples of hydrofluoroethers include 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, and 1,2-bis(1,1,2,2-tetrafluoroethoxy)ethane. An example of an aromatic ether is anisole. Examples of sulfones include sulfolane and methylsulfolane. An example of a cyclic ester is γ-butyrolactone. Examples of linear carboxylic acid esters include acetate, butyrate, and propionic acid. Examples of nitriles include acetonitrile and propionitrile. Organic solvents may be used individually or in combination of two or more.
[0045] The electrolyte is a source of lithium ions, which are the charge transfer medium, and contains lithium salts. Examples of lithium salts include LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(CF3SO2)3, LiN(CF3SO2)2(LiTFSI), LiN(FSO2)2(LiFSI), and LiBC4O8. Lithium salts may be used individually or in combination of two or more types.
[0046] As the solid electrolyte, for example, sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, halogen solid electrolytes, etc., can be used. Examples of sulfide solid electrolytes include Li2S-P2S5 and Li2S-P2S5-LiI. Examples of oxide solid electrolytes include NASICON-type oxides, garnet-type oxides, and perovskite-type oxides. Examples of NASICON-type oxides include oxides containing Li, Al, Ti, P, and O (e.g., Li 1.5 Al 0.5 Ti 1.5 (PO4)3) is one example. Examples of garnet-type oxides include oxides containing Li, La, Zr, and O (e.g., Li7La3Zr2O) 12 Examples include perovskite-type oxides containing Li, La, Ti, and O (e.g., LiLaTiO3).
[0047] There are no particular restrictions on the separator; for example, porous sheets and nonwoven fabric sheets can be used. Examples of porous sheet materials include polyethylene, polyolefins such as polypropylene, aramid, polyimide, and fluororesin. Examples of nonwoven fabric materials include glass fiber and cellulose fiber.
[0048] There are no particular restrictions on the outer casing; known outer casings used for lithium-ion secondary batteries, such as metal containers or laminate film containers, can be used.
[0049] The positive electrode active material for lithium-ion secondary batteries of this embodiment uses a lithium-nickel-manganese composite oxide and does not contain cobalt, thus offering high resource sustainability. Furthermore, since the surface of the lithium-nickel-manganese composite oxide is covered with a boron-containing coating layer at the above coverage rate, the discharge capacity is improved.
[0050] In the positive electrode active material for lithium-ion secondary batteries of this embodiment, the discharge capacity is reliably improved when the boron content forming the coating layer is within the above range. With the positive electrode active material for lithium-ion secondary batteries, the discharge capacity is more reliably improved when the thickness of the coating layer is within the above range.
[0051] In the positive electrode active material for lithium-ion secondary batteries of this embodiment, if the ratio of the thickness of the coating layer to the average particle size of the lithium-nickel-manganese composite oxide is within the above range, the balance between the electrical capacity per particle of the lithium-nickel-manganese composite oxide and the thickness of the coating layer is good, and the discharge capacity is further improved.
[0052] According to the method for producing a positive electrode active material for lithium-ion secondary batteries of this embodiment, since a mixture containing boric acid within the above range is calcined, a positive electrode active material for lithium-ion secondary batteries in which the surface of the lithium-nickel-manganese composite oxide is partially covered with a coating layer containing boron can be produced industrially advantageously. The resulting positive electrode active material for lithium-ion secondary batteries has improved discharge capacity because the surface of the lithium-nickel-manganese composite oxide is covered with a coating layer containing boron at the above coverage rate.
[0053] In the method for producing a positive electrode active material for lithium ion secondary batteries of the present embodiment, when the calcination temperature of the mixture is within the above range, the discharge capacity of the obtained positive electrode active material for lithium ion secondary batteries is reliably improved. In the method for producing a positive electrode active material for lithium ion secondary batteries of the present embodiment, when the temperature rise rate up to the calcination temperature is within the above range, the discharge capacity of the obtained positive electrode active material for lithium ion secondary batteries is more reliably improved. In the method for producing a positive electrode active material for lithium ion secondary batteries of the present embodiment, when the calcination time of the mixture is within the above range, the discharge capacity of the obtained positive electrode active material for lithium ion secondary batteries is further reliably improved. [Examples]
[0054] [Example 1] LiNi with an average primary particle size of 4 μm 0.5 Mn 0.5 O2 powder was prepared. This LiNi 0.5 Mn 0.5 To 99.75 g of the O2 powder, 0.25 g of boric acid powder was added, and the mixture was mixed using a high-speed stirring mixer (Balance Gran, Freund-Turbo Co., Ltd.). The obtained mixture was calcined in an air atmosphere at 300°C for 2 hours using an electric furnace to obtain a calcined powder product.
[0055] [Examples 2 to 3, Comparative Examples 2 to 3] LiNi 0.5 Mn 0.5 A calcined powder product was obtained in the same manner as in Example 1, except that the amount of O2 powder and the addition amount of boric acid powder were set as follows. In Example 2, LiNi 0.5 Mn 0.5 The amount of O2 powder was 99.50 g, and the addition amount of boric acid powder was 0.50 g. In Example 3, LiNi 0.5 Mn 0.5 The amount of O2 powder was 99.25 g, and the addition amount of boric acid powder was 0.75 g. In Comparative Example 2, LiNi 0.5 Mn 0.5 The amount of O2 powder was 99.00 g, and the addition amount of boric acid powder was 1.00 g. In Comparative Example 3, LiNi 0.5 Mn 0.5The amount of O2 powder was set to 97.00g, and the amount of boric acid powder added was set to 3.00g.
[0056] [Comparative Example 1] Without adding boric acid powder, LiNi 0.5 Mn 0.5 O2 powder was calcined in the same manner as in Example 1 to obtain a calcined powder.
[0057] [evaluation] The elemental distribution on the surface of the calcined powders obtained in Examples 1-3 and Comparative Examples 1-3 was measured using XPS, and it was confirmed that the calcined powders obtained in Examples 1-3 and Comparative Examples 2-3 were coated with a boron-containing coating layer. For the calcined powders obtained in Examples 1-3 and Comparative Examples 2-3, in which the boron-containing coating layer was confirmed, the coverage rate and thickness of the coating layer were measured using the method described above. The results, along with the amount of boric acid added during the production of the calcined powders, the calcination temperature, and the calcination time, are shown in Table 1 below.
[0058] 60.0 parts by mass of the powder calcined product obtained in Examples 1-3 and Comparative Examples 1-3 were mixed with 35.8 parts by mass of sulfide solid electrolyte as a solid electrolyte, 2.9 parts by mass of acetylene black (DENKA BLACK Li-100, manufactured by Denka Co., Ltd.) as a conductive additive, and 1.3 parts by mass of SBR (styrene-butadiene rubber) binder. The resulting mixture was dispersed in a solvent to prepare a positive electrode active material slurry. The obtained positive electrode active material slurry was applied to an aluminum foil (current collector) with a thickness of 12.0 μm and dried to produce a positive electrode material. The obtained positive electrode material (working electrode) and metallic lithium foil (counter electrode) were immersed in an electrolyte containing EC, EMC, and DMC in a volume ratio of 3:4:3 and a LiPF6 concentration of 1.2 M to produce a two-electrode cell. The fabricated two-electrode cell was charged at 0.1C with a constant current up to 4.30V, and discharged at a rate of 0.33C with a constant current down to 2.65V.
[0059] [Table 1]
[0060] From the results in Table 1, LiTa 0.5 Mn 0.5 The powder calcined products of Examples 1 to 3, obtained by adding boric acid to O2 powder within the scope of the present invention and calcining, have a coating rate of boron-containing coating layer within the scope of the present invention, and it can be seen that the discharge capacity is improved compared to the powder calcined product of Comparative Example 1, which is not coated with a boron-containing coating layer. This is because LiNi 0.5 Mn 0.5 The reaction between the surface of O2 powder and boric acid produces ion-conductive lithium borate, thereby generating LiNi 0.5 Mn 0.5 This is presumed to be because the O2 powder reduces resistance. On the other hand, the powder calcined products of Comparative Examples 2 and 3, obtained by adding boric acid beyond the scope of the present invention and calcining, showed a lower discharge capacity compared to the powder calcined product of Comparative Example 1, which was not coated with a boron-containing coating layer. This is because the excess boric acid causes unreacted boric acid to react with LiNi 0.5 Mn 0.5 It is presumed that the O2 powder remains on the surface, and this acts as a resistive component, degrading the discharge characteristics.
[0061] [Examples 4-7] A powder calcined product was obtained in the same manner as in Example 1, except that the calcination temperature and calcination time were changed to the conditions shown in Table 2 below. The coverage rate and thickness of the boron-containing coating layer of the obtained powder calcined product, and the discharge capacity were measured in the same manner as described above. The results, along with those of Example 1, are shown in Table 2.
[0062] [Table 2]
[0063] From the results in Table 2, it can be seen that the powder calcined products of Examples 4 to 7, obtained under conditions where the calcination temperature is in the range of 200 to 500°C and the calcination time is in the range of 0.5 to 5.0 hours, have a coating layer coverage within the range of the present invention, similar to the powder calcined product of Example 1, and exhibit improved discharge capacity.
Claims
1. The material comprises a lithium-nickel-manganese composite oxide containing lithium, nickel, and manganese, but without cobalt, and a coating layer that covers a portion of the surface of the lithium-nickel-manganese composite oxide. The coating layer contains boron, A positive electrode active material for a lithium-ion secondary battery, wherein the coverage rate of the coating layer is 40% or more and 90% or less.
2. The positive electrode active material for a lithium-ion secondary battery according to claim 1, wherein the boron content is 0.25% by mass or more and less than 0.75% by mass in terms of boric acid.
3. The positive electrode active material for a lithium-ion secondary battery according to claim 1 or 2, wherein the coating layer contains boric acid.
4. The positive electrode active material for a lithium-ion secondary battery according to claim 1 or 2, wherein the thickness of the coating layer is 5.0 nm or more and 20.0 nm or less.
5. The positive electrode active material for a lithium-ion secondary battery according to claim 1 or 2, wherein the average particle size of the lithium-nickel-manganese composite oxide is 3 μm or more and 5 μm or less.
6. The positive electrode active material for a lithium-ion secondary battery according to claim 1 or 2, wherein the ratio of the thickness of the coating layer to the average particle size of the lithium-nickel-manganese composite oxide is 0.001 or more and 0.014 or less.
7. The positive electrode active material for lithium-ion secondary batteries according to claim 1 or 2, wherein the amount of hydrochloric acid required to neutralize a mixture obtained by adding 1 g of positive electrode active material for lithium-ion secondary batteries to 50 mL of water with 0.05 mol / L hydrochloric acid is 1.8 mL or more and 2.9 mL or less.
8. A method for producing a positive electrode active material for a lithium-ion secondary battery, comprising calcining a mixture containing lithium, nickel, and manganese, but without cobalt, and boric acid, in a ratio such that the boric acid content is 0.25% by mass or more and less than 0.75% by mass.
9. A method for producing a positive electrode active material for a lithium-ion secondary battery according to claim 8, wherein the calcination temperature of the mixture is 200°C or more and 500°C or less.
10. A method for producing a positive electrode active material for a lithium-ion secondary battery according to claim 9, wherein the material is heated to the aforementioned firing temperature at a heating rate of 5°C / min or more and 20°C / min or less.
11. A method for producing a positive electrode active material for a lithium-ion secondary battery according to claim 8 or 9, wherein the calcination time of the mixture is 0.5 hours or more and 5.0 hours or less.
Citation Information
Patent Citations
Positive electrode active material for lithium ion secondary battery, and method for manufacturing the same
JP2021064598A
Positive electrode active material, manufacturing method thereof, secondary battery, battery module, battery pack and device
JP2023513558A